(untitled) (Research, Society and Development, 2022)
This study aims at a compilation of the assistance provided by the nursing team during the period of the female reproductive cycle, aspects of women’s health during the puerperal phase. From this, a narrative literature review was carried out, in view of the search for scientific articles in the Bireme, SCielo and PubMed databases. How to identify nursing care for puerperal women, still reflecting compliance with patients, who feel comfortable and confident under nursing care after childbirth rejection There is no inclination to abandon patients given that the results of the review postpartum is still a common reality. It is up to the study to further research, especially in the education gap in pregnant women about their children and who do not end at the time of delivery, and as for those, it is important that there is continued health on the rights of the puerperium, to improve more and more the care offered to women. this audience.